2011
DOI: 10.1007/s00431-011-1453-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids in the treatment of neonatal meconium aspiration syndrome

Abstract: Meconium aspiration syndrome is a serious neonatal disease with complex pathophysiology. With respect to the contribution of meconium-induced lung edema, inflammation and vasoconstriction on the course of the disease, glucocorticoids are increasingly used in the treatment of MAS despite the fact that principal questions on the choice of GCs derivative, mode of delivery and dosing have not been answered yet. To bring a complex insight into the topic, this article reviews the pathomechanisms of MAS, mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 82 publications
(124 reference statements)
1
32
1
Order By: Relevance
“…Hydrocortisone also increased cGMP by normalizing sGC and PDE5 activity and by attenuating abnormalities induced by oxidative stress [18]. Brief courses of glucocorticoids may be beneficial, particularly in severe MAS in the presence of lung edema, pulmonary vasoconstriction and inflammation [71]. However, the usual precautions must be exercised when considering steroids in neonates.…”
Section: Emerging and Novel Treatment Strategiesmentioning
confidence: 99%
“…Hydrocortisone also increased cGMP by normalizing sGC and PDE5 activity and by attenuating abnormalities induced by oxidative stress [18]. Brief courses of glucocorticoids may be beneficial, particularly in severe MAS in the presence of lung edema, pulmonary vasoconstriction and inflammation [71]. However, the usual precautions must be exercised when considering steroids in neonates.…”
Section: Emerging and Novel Treatment Strategiesmentioning
confidence: 99%
“…Budesonide used with high frequency jet ventilation was found to be better with minimal extra-pulmonary losses 4 . Tripathi et al 1,5 reported better oxygenation and reduced hospital stay with intra-tracheal budesonide.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage with budesonide was the route of administration. It was administered through intratracheal route in rabbits and effects were much better and it alleviated side effects noticed by systemic dexamethasone, like heart rate variability with reduction of oxidation injury to lungs 4,8 . Basu et al in their trial on newborns, used nebulized budesonide and compared it with systemic methylprednisolone and control group (no steroid group) of newborns and found steroids useful with no toxic effects irrespective of route of administration 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations